Prosedur Pemberian Pinjaman Kredit Pada Primkopal Komando Pendidikan Marinir Surabaya (Laporan Kegiatan Kuliah Kerja Lapangan) - Miftaqul Sandrina Wardani; Wiratna Wiratna; Sutini Sutini; Diana Zuhro; Tjandra Wasesa; Heri Toni (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
The beginning of the word credit comes from Latin, namely "Credere" which means trust, which is the trust of the creditor that the debtor will return the loan and interest in accordance with the agreement of both parties. According to the Banking Law, credit is the provision of money or bills that can be likened to it, based on an agreement or loan agreement between a bank and another party, which requires the borrower to pay off its debt after a certain period of time with interest. Various forms of credit according to OJK (Financial Services Authority) such as unsecured credit loans (KTA), Credit Cards, Motor vehicle loans, Business loans. One of the most popular forms of credit is bank or financial credit, it credits money to borrowers who must pay it back in the future. Primkopal Marine Education Command Surabaya is a cooperative whose one of its business units is the Savings and Loans Business (USP). The Primkopal of the Surabaya Marine Education Command serves or requires its members to save, in addition to being able to provide credit to its members. The crediting process is inseparable from the crediting procedures carried out, for this reason, the cooperative management must provide integrated crediting procedures to make it easier for members to follow each credit granting procedure. Credit procedures are used as an effort to minimize the occurrence of bad loans, where bad loans that occur directly disrupt the operational activities of the cooperative. Hasibuan stated that controlling credit management (2006: 105) is an effort to keep the credit provided smooth, productive, and not bad. The credit management control system aims to avoid abuse of authority by various parties concerned and avoid unhealthy lending practices, so that the risk of bad loans in cooperatives can be minimized and not exceed credit health standards.